High concentrations of several metabolites and growth factors in patients with delayed lower limb fracture healing - Maksim V. Stogov; Anatolii G. Karasev; Elena A. Kireeva; Natalia V. Tushina (Гений oртопедии, 2018)
Purpose To study concentrations of metabolites and growth factors as well as hematological parameters in patients with delayed lower limb fracture healing Material and methods Concentrations of several metabolites and growth factors as well as hematological parameters were studied in 13 patients with a delay in healing of femoral and tibial fractures after 7 to 11 months following injury. Seven patients with consolidated diaphyseal femoral and tibial fractures examined 10 to 12 months after the injury were a control group. Ten healthy subjects that did not have any history of fractures were a reference group. Results Unlike individuals of control and reference groups, patients with delayed fracture healing showed significantly higher concentrations of lactate, triglycerides, TGF-α and TGF-β2 in their serum while IGF-1 levels were significantly lower. Hematology tests did not show differences between the groups. Conclusion Local hypoxia, acidosis and expression of GFs that support osteolysis were the main pathophysiological processes that could cause the delay in long-bone fracture healing.